Early Maturing Wheat Genotypes for Better Integration in Rice-Wheat Cropping Systems in Kashmir Valley of Western Himalayas: Genetic Evaluation of Wheat Genotypes for Earliness and Yield-Related Traits - Mir, Reyazul Rouf; Rathore, Mukesh; Aggarwal, Nikita; Jan, Farkhandah; Shafi, Safoora; Tahir, Mohd.; Bhat, Mohd. Ashraf; Khan, Mohd. Anwar; Sofi, Parvaze Ahmad (Journal of Cereal Research, 2025)
Wheat productivity in the temperate Himalayan region of the Kashmir Valley remains low due to recurring early-season cold stress, which delays phenological development and disrupts the timely rice–wheat cropping system. To address this challenge, 20 diverse wheat genotypes, including two regional checks (Shalimar Wheat-1 and Shalimar Wheat-2), were evaluated across five cropping seasons (2020–2025) under temperate field conditions at Wadura, SKUAST-Kashmir. Eight key agro-morphological traits—days to 50% flowering, days to maturity, plant height, spike length, spikelets per spike, grains per spike, estimated grain yield, and thousand-grain weight, were assessed to quantify phenotypic and genetic variation. Pooled ANOVA revealed significant effects of genotype, environment, and genotype × environment interaction for most traits, highlighting substantial diversity and environmental influence. Considerable phenotypic variation was recorded across all traits. Genotypes WW-103, WW-101, and WW-102 consistently exhibited the earliest flowering and maturity, with WW-103 achieving the highest yield (4.69 t ha⁻¹), outperforming the checks. PCV values exceeded corresponding GCV values, indicating environmental modulation, while high heritability (76.97 to 97.37 %) confirmed strong genetic control. Positive correlations among spike-related traits and yield emphasized their importance under temperate conditions. Overall, WW-101, WW-102, and WW-103 show strong potential as early-maturing, high-yielding candidates suited to the Kashmir Valley’s cold-prone climate and for strengthening rice–wheat cropping system adoption.